PENERAPAN MODEL PEMBELAJARAN METAPHORMING UNTUK MENINGKATKAN KREATIVITAS BERPIKIR DALAM BELAJAR SISWA PADA MATA PELAJARAN FIKIH KELAS XI DI MAN 2 PALEMBANG - Popi Septasari; Muhammad Isnaini; Baldi Anggara (PAI RAFAH, 2021)
This research was conducted based on cases in the field where students did not provide many statements and questions before the teacher asked questions, students saw problems from the same point of view as other friends, students were less than optimal in generating new ideas, and from existing ideas students had not optimally developed them. Therefore, the metaphorming learning model will be applied to increase the creativity of students' thinking. This research is an experimental research (true experimental design) with an approach quantitative. The research design used a pretest-posttest control group design. The research subjects were students of class XI MAN 2 Palembang with sample selection through probability sampling (cluster random sampling). The research instruments used were tests and observations. The test used is a test of description and observation. The method of analysis uses the normality test which aims to determine whether the data comes from normally distributed samples, the homogeneity test is to ensure that the data comes from a homogeneous population. If the data is normally distributed and homogeneous then it is continued by using the t-test. Data is normally distributed and homogeneous. The results of hypothesis testing using the ttest at the 0.05 level of confidence obtained tcount = -1.303 and ttable = 1.671. Then the value of tcount < ttable. In the pretest Ho was accepted and Ha was rejected or there was no significant difference between the experimental class and the control class because they had not been given treatment. The posttest hypothesis testing obtained tcount = 11,129 and ttable = 1,670. Then the value of tcount > ttable. It can be concluded that in the posttest Ho is rejected and Ha is accepted or there is a significant difference between the control class and the experimental class.